Online field experiments. Issue 3 (4th May 2019) - Muise, Daniel; Pan, Jennifer
ABSTRACT: Changes in information communication technology across the Asian region have altered our field substantively and methodologically. The rapid growth of digitized communications allows us to find new purchase in examining questions fundamental to our understanding of communication theories, norms, and practices across Asia. While methods such as text mining and user analytics are increasingly popular among computational scholars, here, we focus on online field experiments, an approach to studying communication that has the potential to overcome many existing obstacles to social scientific inquiry but one that has been used relatively rarely in Asia. In this paper, we discuss what online field experiments are and how they differ from traditional experiments as well as online lab and survey experiments. We show how researchers can go about designing and implementing online field experiments, focusing on issues where online field experiments differ from their traditional counterparts – legal and ethical considerations, construct validity, randomization and spillover, and statistical analyses. Finally we discuss how online field experiments can advance our understanding of communication in Asia by helping researchers to gain insight and make causal inferences on attitudes, behaviors, and interactions that were previously unobservable ℘.